2001
DOI: 10.1097/00006123-200112000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Postischemic Intravenous Administration of Magnesium Sulfate Inhibits Hippocampal CA1 Neuronal Death after Transient Global Ischemia in Rats

Abstract: These results demonstrate a neuroprotective intravenous dose of MgSO(4), which is effective when administered before or late after ischemia, and a previously uncharacterized dose-response curve for MgSO(4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…We also used MgSO 4 . Similar to our results, previous studies [29][30][31] have also found that MgSO 4 treatment had a neuroprotective effect in cerebral ischemia.…”
Section: Discussionsupporting
confidence: 93%
“…We also used MgSO 4 . Similar to our results, previous studies [29][30][31] have also found that MgSO 4 treatment had a neuroprotective effect in cerebral ischemia.…”
Section: Discussionsupporting
confidence: 93%
“…Magnesium, the second most common intracellular cation and the most abundant intracellular divalent cation (32)(33)(34), has been shown to be neuroprotective in several experimental models of ischemic and excitotoxic brain injury (20,21). However, other studies have failed to detect a neuroprotective effect of magnesium (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium sulfate has been shown to be neuroprotective in several experimental models of ischemic brain injury (Lampl et al, 2001;Izumi et al, 1991;Kaya et al, 2001;Miles et al, 2001;Yang et al, 2000;Şirin et al, 1998;Marinov et al, 1996;Chung et al, 2004). This effect may be due to the inhibition by Mg 2+ of the mitochondrial permeability transition (Zoratti and Szabò, 1995).…”
Section: Introductionmentioning
confidence: 99%